Youth Baseball Coach Awareness of Pitch Count Guidelines and Overuse Throwing Injuries Remains Deficient. Issue 10 (November 2018) - Knapik, Derrick M.; Continenza, Sara M.; Hoffman, Kyle; Gilmore, Allison
Abstract : Background: Baseball is one of the most popular youth sporting activities. Youth pitchers remain at high risk for shoulder and elbow overuse injuries despite well-established recommendations on pitch count limits. The purpose of this investigation was to conduct surveys of youth baseball coaches evaluating the current state of understanding and compliance with youth pitch count guidelines and risk factors for overuse injuries. Methods: A total of 82 youth baseball coaches in surrounding suburban areas outside 2 separate Midwestern metropolitan cities were asked to answer an anonymous 13-question survey. Survey questions solicited demographic information of youth athletes coached, while assessing for incidence, knowledge of, and compliance with established recommendations on pitch count limits and upper extremity overuse injuries in youth pitchers. Results: In total, 61 of 82 (74%) coaches returned surveys. The majority of coaches reported coaching male athletes (89%, n=54) primarily between the ages of 11 to 12 years (51%, n=31). A total of 56% (n=34) of coaches reported "always" keeping track of pitch counts; however, 92% (n=56) reporting not keeping track of pitches based on established recommendations by the American Sports Medicine Institute, whereas 56% were noncompliant with age appropriate pitch count recommendations as established by the 2006 US Baseball Medical and Safety Advisory Committee. Only 13% (n=8) of coaches were able to correctly identify risk factors for overuse injuries while acknowledging the necessity of off-season strengthening. Thirty-eight percent (n=23) of coaches reported sitting out an athlete because of overuse injury, with the highest rates found in those coaching the youngest (⩽8 and younger) and oldest (≥17 and older) age groups. Meanwhile, 15% (n=9) of coaches were noncompliant with age-based recommendations against throwing breaking pitches. Conclusions: Knowledge regarding pitch count guidelines established to prevent overuse injuries to the shoulder and elbow in youth pitchers remains deficient in the cohort of coaches surveyed. Level of Evidence: Level IV—Case Series.